Hubungan Variasi Mengajar Guru Dengan Motivasi Belajar Siswa Kelas VIII Pada Mata Pelajaran Pendidikan Agama Kristen Di SMP Negeri 2 Harian T.A.2023/2024. - Rinaldi Sihotang; Elvri Teresia Simbolon; Frainskoy Rio Naibaho; Rusmauli Simbolon; Senida Harefa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The problems in this research are: 1) what are the variations in teaching of Christian Religious Education teachers in class VIII of SMP Negeri 2 Harian T.A 2023/2024, 2) what is the learning motivation of class VIII students in the Christian Religious Education subject at SMP Negeri 2 Harian T.A 2023/ 2024, 3) Is there a positive and significant relationship between variations in teacher teaching and the learning motivation of class VIII students in the Christian Religious Education subject at SMP Negeri 2 Harian T.A 2023/2024?. The aims of this research are 1) to determine the variations in teaching of Christian Religious Education teachers in class VIII of SMP Negeri 2 Harian T.A 2023/2024, 2) to determine the learning motivation of class VIII students in the Christian Religious Education subject at SMP Negeri 2 Harian T.A 2023/2024 , 3) to determine the relationship between teacher teaching variations and the learning motivation of class VIII students in the Christian Religious Education subject at SMP Negeri 2 Harian T.A 2023/2024. This research includes correlational research. The population in this study was all 30 students in class VIII of SMP Negeri 2 Harian. Data collection in this research was carried out using a closed questionnaire. The data analysis technique uses the product moment correlation formula and t-test. a) a positive relationship test obtained a value of rxy = 0.595 rtable (a=0.05; IK=95%; n=30) namely 0.361, thus a positive relationship between variable X and variable Y. b) a significant relationship test was obtained The value of tcount > ttable is 3.918 > 2.048, thus it can be seen that there is a significant relationship between variable Christian Religious Education at SMP Negeri 2 Harian FY 2023/2024. acceptable.